Determinants of Outward Foreign Direct Investment from Singapore and its Impacts on Economic Growth - Leong, Shi Ting (2017)
This study comprises of two primary objectives. First, this study examines the pattern of Singapore’s outward foreign direct investment (OFDI) and sheds light on the determinants of OFDI originated from Singapore to top destination host countries covering the period 1994 to 2014, by employing ARDL approach on time series data. A review of Singapore’s economic development and government policies towards OFDI is presented to provide a fundamental and background framework to understand the emergences and growth of Singapore’s OFDI. Theoretical and empirical evidences are discussed to provide analytical and theoretical background in examining Singapore’s OFDI. In the second part, the study employs bounds testing ARDL approach to cointegration and Granger causality test to identify the dynamic interaction between Singapore’s OFDI and its economic growth, as well as incorporating the effect of crisis. Finally, the study ends with suggestions of policy implications and future prospects.